Identification of a New Compound as α-Glucosidase Inhibitor from Aspergillus aculeatus - Dewi, Rizna Triana; Suparman, Asep; Mulyani, Hanny; Darmawan, Akhmad; Lotulung, Puspa Dewi N. (Annales Bogorienses, 2016)
Terestrial fungi are of great importance as potential sources of pharmaceutical agent. Aspergillus aculeatus, a fungus isolated from soil sample collected in Indonesia, was cultured in liquid media to investigate a novel compound as inhibitor -glucosidase. The mycelium extract of A. aculeatus shows potential activity against Saccharomyces cereviseae -glucosidase and mild activity against mammalian -glucosidase with IC50 values of 9.57 μg/mL and 470.76 mg/mL, respectively. Enzyme assay-guided fractionation of this extract afforded rubrofusarin (1). Rubrofusarin, a linear naphtho--pyrone, is a natural pigment from Aspergillus sp. Interestingly, compound 1 shows potential inhibitory activity against mammalian -glucosidase (IC50 of 92.7 μg/mL), but no to S. cereviseae -glucosidase. The results suggest that A. aculeatus is a promising natural source as a lead compound in the discovery of antidiabetic drug.